Formulasi Sediaan Gummy Candies Sari Brokoli (Brassica Oleracea L.) Dengan Variasi Sukrosa Sebagai Pemanis - Niza Fonna, Gabena Indrayani Dalimunthe (Journal of Health and Medical Science, 2022)
Broccoli belongs to the cabbage family and includes vegetables that are not resistant to hot air. Broccoli is efficacious to accelerate the healing of the disease and prevent and inhibit the development of cancer cells in the body, especially hormone-related cancers, such as breast cancer in women, and prostate cancer that threatens men. Therefore, it is very potential to be developed and made in gummy candies preparations so that consumers can be consumed for all ages (especially children). The objective of the research was to find out broccoli essence can be formulated into gummy candies with variations of sucrose as sweetener, test the quality of broccoli candies gummy candies preparations resulting from various physical tests and the results of the favorite level of gummy candies from broccoli essence with variations in sucrose levels as sweetener. In this research used formula 1 with the amount of sucrose levels 115 mg, formula 2 with the amount of sucrose levels 230 mg, formula 3 with the amount of sucrose content 345 mg, formula 4 with the amount of sucrose content 460 mg and formula 5 with the amount of sucrose levels 575 mg. Based on the results of the research, broccoli essence could be formulated into gummy candies preparations with sucrose variations, had an attractive shape and color with a distinctive odor, as well as a chewy texture and has a pH of 5 that was suitable for gummy candies, the results of the favorite level test showed formula 5 was the preferred one with a variation in sucrose levels of 575 mg. Variations in sucrose levels had an effect on the level of liking.